Identitas nasional sebagai benteng ketahanan budaya lokal dari pengaruh asing - zahrotus, Dara (Maliki Interdisciplinary Journal, 2025)
National identity represents the collective values, culture, and history of a nation and serves as a foundation for maintaining sovereignty and unity. In the context of Indonesia, national identity is reflected not only in state symbols but also in the country’s rich and diverse local cultural heritage. This cultural diversity strengthens the spirit of nationalism and becomes a crucial element of social cohesion. In the era of globalization, however, local cultures face significant challenges due to the influx of foreign influences through media, technology, and trade. Uncontrolled cultural assimilation may weaken local values and erode the nation’s identity. Therefore, reinforcing national identity is vital as a cultural defense mechanism to protect local heritage from the negative impacts of foreign culture. Efforts to preserve local culture must go hand in hand with instilling nationalist values from an early age through education, cultural policies, and community engagement. By strengthening national identity, Indonesia can safeguard its local cultures as irreplaceable treasures while selectively adapting to global influences.